Adolescents in Quarantine During COVID-19 Pandemic in Italy: Perceived Health Risk, Beliefs, Psychological Experiences and Expectations for the Future - Commodari, Elena; La Rosa, Valentina Lucia (Frontiers in Psychology, 2020)
Since March 2020, many countries throughout the world have been in lockdown in response to the COVID-19 pandemic. In Italy, the quarantine began on March 9, 2020, and containment measures were partially reduced only on May 4, 2020. The quarantine experience has a significant psychological impact at all ages but can have it above all on adolescents who cannot go to school, play sports, and meet friends. In this scenario, this study aimed to provide a general overview of the perceived risk related to COVID-19 and the psychological experience of quarantine in a large sample of Italian adolescents. 978 adolescents (males = 339; females = 639) living in 13 Italian regions and attending upper secondary school (age range: 13–20, M = 16.57, SD = 1.20), responded to an internet-based questionnaire about perceived health risk related to COVID-19, knowledge and information on measures to control the pandemic, beliefs and opinions on stage two of the quarantine, and psychological experiences related to quarantine. 31.1% of the participants lived in "red zones," which are places where the government has imposed stricter measures of containment due to exponential and uncontrolled growth in contagion cases compared to other areas in Italy. According to our results, Italian adolescents had a low perception of risk of COVID-19. Perceived comparative susceptibility and perceived seriousness were also very low. However, they were aware of the restriction measures necessary to contain the spread of the virus, and they agreed with the limitations imposed by the government. Females and adolescents living in a “red zone” showed more significant psychological negative feelings about the quarantine experience. However, no significant differences were found about the regions where the teenagers of our sample live and the other variables related to the COVID-19 experience. This is very interesting data, leading us to hypothesize that the participants' negative feelings may be more related to the adolescent period than to the pandemic itself.